PENGARUH MODEL INKUIRI TERBIMBING TERHADAP KETERAMPILAN PROSES SAINS DI SMAS SANTO FRANSISKUS ASISI PONTIANAK - Sawe, Agustina Sekunda; Harun, A. Ifriany; Rasmawan, Rahmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research have the purpose to determine skill differentiation of science process, before and after studying guided inquiry learning model at salt hydrolysis material. This research also have the purpose to know the impact of science process skill of the  XI MIPA SMAS Santo Fransiskus Asisi Pontianak students. This research used pre-experimental design method with design One-Group Pretest-Posttest. Data collecting  were executed by measuring technique, direct observation, and direct communication. Wilcoxon result  showed that there are differentiation between science process skill of the students before and after the application of guided inquiry learning model. By using effect size Glass,  the calculation result showed that there are the influence of science process skill of the students before and after the application of guided inquiry learning model about 80,98%.  Keywords: Guided Inquiry, Science Process Skill, and Salt  Hydrolysis.